2018
DOI: 10.4155/fmc-2018-0072
|View full text |Cite
|
Sign up to set email alerts
|

Sigma-2 Receptor: Past, Present and Perspectives on Multiple Therapeutic Exploitations

Abstract: Identification of sigma-2 receptor (sig-2R) has been controversial. Nevertheless, interest in sig-2R is high for its overexpression in tumors and potentials in oncology. Additionally, sig-2R antagonists inhibit Aβ binding at neurons, blocking the cognitive impairments of Alzheimer's disease. The most representative classes of sig-2R ligands are herein treated with focus on compounds that served to study sig-2R biology and to produce sig-2R: fluorescent ligands; multifunctional anticancer agents; and targeting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 93 publications
0
39
0
Order By: Relevance
“…Abate and colleagues have employed a variety of approaches to generate these compounds and have produced fluorescent S2R ligands, nanoparticles that can be used as tools in S2R research, and multi-target agents intended to have cytotoxic effects (Abate, Niso and Berardi, 2018;Abate et al, 2019). To accomplish these goals, the lead compounds were decorated, in the appropriate position, with alkyl linkers bridging the pharmacophore from either a fluorescent tag or a fluorescent nanoparticle as the quantum dot (Abate et al, 2011(Abate et al, , 2014Niso et al, 2015;Pati et al, 2017).…”
Section: Development Of S2r Ligandsmentioning
confidence: 99%
“…Abate and colleagues have employed a variety of approaches to generate these compounds and have produced fluorescent S2R ligands, nanoparticles that can be used as tools in S2R research, and multi-target agents intended to have cytotoxic effects (Abate, Niso and Berardi, 2018;Abate et al, 2019). To accomplish these goals, the lead compounds were decorated, in the appropriate position, with alkyl linkers bridging the pharmacophore from either a fluorescent tag or a fluorescent nanoparticle as the quantum dot (Abate et al, 2011(Abate et al, , 2014Niso et al, 2015;Pati et al, 2017).…”
Section: Development Of S2r Ligandsmentioning
confidence: 99%
“…Sigma-2 receptors, lately identified as TMEM97 proteins, are overexpressed in diverse types of cancers and their modulation leads to cell death upon the activation of a number of still investigated pathways [35][36][37][38][39][40][41][42][43][44][45]. Several sigma-2 receptor high-affinity ligands have been developed during recent decades (and lately reviewed), revealing cytotoxic activity through pathways that appear to be molecule-dependent and cell-type-dependent, with mechanisms that span from caspase-dependent apoptosis, autophagy, increase in ROS, and mithocondrial superoxide production [36,37,40,44]. Some sigma-2 ligands were surprisingly found to be able to kill doxorubicin-resistant cells more than the non-resistant counterparts (breast cancer cells MCF7/DX over MCF7 cells, non-small cell lung cancer A549/DX over A549 cells, colon cancer HT29/DX over HT29 cells) [28,29,33].…”
Section: Introductionmentioning
confidence: 99%
“…Three compounds, derived from three different classes of sigma-2 receptor ligands ( Figure 1: [41]; and F400 6,7-dime thoxy-2-[3-(5-methoxy-1,2,3,4-tetrahydronaphthalen-1-yl)propionyl]-1,2,3,4 tetrahydroisoquinoline) [42] emerged as MRP1 modulators in the preliminary screening and for this reason they were further evaluated in the appropriate MDR cell line models and in a preclinical in vivo model. affinity ligands have been developed during recent decades (and lately reviewed), revealing cytotoxic activity through pathways that appear to be molecule-dependent and cell-type-dependent, with mechanisms that span from caspase-dependent apoptosis, autophagy, increase in ROS, and mithocondrial superoxide production [36,37,40,44]. Some sigma-2 ligands were surprisingly found to be able to kill doxorubicin-resistant cells more than the non-resistant counterparts (breast cancer cells MCF7/DX over MCF7 cells, non-small cell lung cancer A549/DX over A549 cells, colon cancer HT29/DX over HT29 cells) [28,29,33].…”
Section: Introductionmentioning
confidence: 99%
“…[ 3 H](+) − pentazocine exhibits a high a nity for σ1R, whereas [ 3 H]DTG binds with equal a nity to both σ1R and σ2R. Subsequent studies have revealed that these proteins are also involved in intracellular ion regulation and neuron survival [1,4,[6][7][8].…”
Section: Introductionmentioning
confidence: 99%